Agronomic biofortification of garlic (Allium sativum L.) through strategic foliar application of zinc sulphate and borax under subtropical conditions of Jammu - Diksha, R; Manoj, K; Satesh, K; Bazaya, B R; Singh, S P; Samnotra, R K; Sandeep, C; Anil, B; Neha, K (Plant Science Today, 2026)
Despite the well-known benefits of zinc and boron biofortification in improving nutritional content and quality in garlic, there is no established optimum application approach for zinc and boron micronutrients under Jammu's subtropical climate. Therefore study was carried out to investigate the potential of zinc and boron biofortification in the garlic crop to enhance the nutrient content. The favourable effects of zinc and boron on the productivity and qualitative attributes of garlic underscore the necessity to determine a standardized optimal dosage of these micronutrients. The SJG-16-01 garlic genotype was utilised to optimize crop output. Sowing was done in the month of October with a spacing of 15 × 10 cm. The research comprised 16 treatments, each replicated thrice inside a randomised complete block design (RCBD) during the Rabi season of 2022-23. Zinc sulphate and borax were applied as foliar sprays 45 and 60 days after planting, at doses of 0.25, 0.5 and 0.75 %, both separately and in conjunction. Vegetative growth data were recorded at various time intervals to study the growth of the crop with the application of zinc sulphate and borax. The findings indicated that the application of a combination of zinc sulphate (0.5 %) and borax (0.25 %) twice, at 45 and 60 days post-planting, enhanced the growth, production and quality of garlic as represented by cell plot analysis. Vegetative growth data were recorded at various time intervals to study the growth of the crop with the application of zinc sulphate and borax. The mineral content of zinc and boron was also enhanced with the application of treatments. Nonetheless, the identical treatment concurrently improves the productivity and profitability of the crop in the subtropical circumstances of Jammu.